Hydrogen production by Chlamydomonas reinhardtii in a two-stage process with and without illumination at alkaline pH - Saleem, M.; Chakrabarti, M.H.; Abdul Raman, Abdul Aziz; Hasan, D.B.; Daud, Wan Mohd Ashri Wan; Mustafa, A. (2012)
This work presents the results of a two-stage (carbon fixation and hydrogen production) experimental study for hydrogen production from microalgae using optical fiber as an internal light source. Effect of absence and presence of light on Chlamydomonas reinhardtii culture's pH shift is also evaluated. The culture pH value is a function of light intensity; the pH in the alkaline range changes from 7.5 to 9.5 in the presence and absence of optical fiber respectively. The maximum rate of hydrogen production in the presence of exogenic glucose and optical fiber is 6 mL/L-cult/hour, which is higher than other reported values. This study has also revealed that the presence of light reduces the lag time for hydrogen production from 12 to 5 h. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.